On the occurrence of rainfall over southwest sector of monsoon depression - RAJAMANI, S.; RAO, K. V. (MAUSAM, 1981)
The generally observed feature that there is good rainfall activity in the southwest sector of the monsoon depression when it moves northwestwards/westnorthwestwards and in the northeast sector of the monsoon depression when, after recurvature, it moves northwards/northeastwards has been explained on the basis of w-equation. The generally observed feature that there is good rainfall activity in the southwest sector of the monsoon depression when it moves northwestwards/westnorthwestwards and in the northeast sector of the monsoon depression when, after recurvature, it moves northwards/northeastwards has been explained on the basis of w-equation.